Age, growth and reproductive biology of a widespread coral reef fish, yellowfin goatfish Mulloidichthys vanicolensis (Valenciennes, 1831) - Samejima, Shota; Tachihara, Katsunori (Journal of Fish Biology, 2022)
Yellowfin goatfish Mulloidichthys vanicolensis (Valenciennes, 1831) is a widely distributed commercial fish in the Indo‐Pacific. The authors examined the age, growth, sexual maturity and spawning season of M. vanicolensis around Okinawa Island, southwestern Japan, based on sectioned otolith and gonadal histology. Monthly changes in the appearance of an opaque edge indicate the annual formation of otolith bands. This fish shows sexual size dimorphism due to the faster growth and larger size of females compared to males. The von Bertalanffy growth functions were Lt = 31.0{1 – exp(−0.39(t + 1.62))} for females and Lt = 28.3{1 – exp(−0.42(t + 1.45))} for males. This species has a short life span, with a maximum age of 7.75 years, and reaches maturity in its first year of life. Observed fork lengths at 50% maturity were 19.4 cm for female and 16.2 cm for male. The main spawning season occurs from May to October. The authors compared their findings with those of previous studies on the life‐history characteristics of M. vanicolensis. Spawning season, growth and maturity size differed from those found in previous studies in areas with genetic continuity. Differences in life‐history traits between genetically continuous populations suggest a high degree of environmental adaptability for this species, which may be one of the reasons for its widespread distribution.